IMPACT OF WATER STRESS ON COTTON PHYSIOLOGY, ROS ACCUMULATION AND ANTIOXIDANT ACTIVITY IN UPLAND COTTON GENOTYPES - HUSSAIN, A; JAMIL, S; BILAL, M; NADEEM, A; KAUSAR, S; UMER, F; AKRAM, F; HAQ, AUL; QUYUM, MA; BUTT, B; et al. (Biological and Clinical Sciences Research Journal, 2024)
The current study was designed to compare the performance of ten cotton strains based on their key morphological, physiological, biochemical, antioxidant, and fiber quality-related traits under water stress conditions. The experiment was laid out under RCBD with three replicates and a 75 cm row-to-row distance was maintained. The data was recorded for CLCuV percentage, whitefly attack percentage, sympodia per plant, boll weight, ginning out turn, net photosynthetic rate, transpiration rate, stomatal conductance, cotton yield, total oxidative stress, sugars, ascorbic acid, total antioxidant capacity, glycine betaine, peroxidases, fiber length, fiber fineness, fiber strength, and fiber uniformity. The results revealed the occurrence of significant variations for agronomically important and fiber quality-related traits in cotton strains under water stress conditions except for boll weight. The correlation coefficient analysis revealed a strong positive correlation of cotton yield with transpiration rate, sugars, ginning out turn, stomatal conductance, peroxidases, net photosynthetic rate, and glycine betaine while a strong negative correlation with total oxidative stress, total oxidative stress, fiber fineness and fiber strength under water stress conditions. The PC-1/PC-2 based biplot analysis reconfirms the results obtained through the correlation analysis and further unveiled that most of the variations in the data were due to CLCuV percentage, fiber fineness, net photosynthetic, transpiration rate, ginning out turn, seed yield and total oxidative stress. The cluster analysis categorizes ten cotton strains into four clusters and found that cotton strains CRS-2202, CRS-2201, and CRS-2204 were the most productive.